BIOMOLECULAR ASPECTS AND UPDATE ON TREATMENT OF CEREBRAL MALARIA - Husna, Machlusil; Prasetyo, Bowo Hery (Malang Neurology Journal, 2016)
Malaria is still becoming a health problem in the world and in Indonesia. Cerebral malaria is one of many features of severe and life threatening malaria. Many hypotheses underlying the pathophysiology of cerebral malaria have been disclosed, but the one that evolved nowdays is the hyphotesis of mechanical, permeability, humoral, and MMPs. These hypotheses proposed about biomolecular aspects of cerebral malaria and the mechanism is still not well understood. The understanding of this pathophysiology will aid the treatment of cerebral malaria. Current basic treatment of cerebral malaria is the ACT (artemisinin base combination treatment) drugs, supportive treatment and the management of its complications which is indispensable. Many research has been conducted and still in progress for finding the best optimal treatment.